Ultra‐High Transmission Broadband Tunable VO2 Optical Limiter. Issue 4 (26th January 2023) - Guan, Huan; Ren, Feifei; Liang, Shuhui; Gu, Jinxin; Geng, Chenchen; Wei, Hang; Dou, Shuliang; Zhao, Jiupeng; Li, Yao
Abstract: An optical limiter (OL) is a nonlinear device that protects sensitive photodetectors or human eyes from high‐intensity illumination. However, current OLs have low open‐state transmittance and a limited turndown ratio in some cases. In this study, first it is demonstrated that combining the insulator‐to‐metal transition (IMT) of vanadium dioxide (VO2 ) with anti‐reflection layers can enable both high and broadband open‐state transmittance (>−0.9 dB at the peak wavelength) while preserving a large turndown ratio (>21.8 dB). Furthermore, optothermal simulation is conducted to analyze the performance of the VO2 OL under ultrafast laser irradiation. The result reveals that IMT of the VO2 OL occurs at 0.23 µs when the incident laser intensity is 90 kW cm −2 . These benefits offer a promising alternative to OLs in technologies ranging from sensor protection to human eye defense. Abstract : Ubiquitously growing high‐power light sources can damage delicate optical components and human eyes. Therefore, transmissive optical limiters (OLs) integrating VO2 with double‐sided HfO2 anti‐reflection layers are designed and demonstrated to realize ultra‐high transmittance in the open‐state while also providing a large turndown ratio. These benefits provide a new platform for realizing facilely tunable OLs in infrared imaging and laser protection.